APLIKASI PERSAMAAN DIFERENSIAL PADA MODEL PERTUMBUHAN POPULASI DENGAN PERTUMBUHAN TERBATAS - Rina, Iswan; Husna, Radhiatul (Sainstek : Jurnal Sains dan Teknologi, 2019)
Differential equations are one of the topics in mathematics that have many applications in mathematical modeling, for example in population growth. Population growth is an important thing that needs to be considered in order to be able to see the development of an area so that it can assist the regional government in determining the policies taken for the progress of the region related to the potential growth of the existing population. In this paper we will study population growth models with limited growth. From this model, the population of a region can be predicted in the coming year